Impact of Poverty Alleviation Fund’s Revolving Fund for Income Generation Programme in Lalbandi, Sarlahi - Timilsina, Umesh; Dhakal, Anju (Janajyoti Journal, 2024)
This study has been conducted to evaluate the management, efficiency, and effect of the Poverty Alleviation Fund’s revolving fund for Income Generating Program in Lalbandi Sarlahi. It aimed at eradicating absolute poverty and reducing relative poverty in community organizations at Lalbandi Municipality. The study employed research methods such as field observations, surveys, and group discussions. Although the program is faced with challenges including uneven income distribution among members of the organization and climate change resilience, this does not deter it from supporting 15 community-based organizations which received NPR 32,553,675.50 as of the fiscal year 2075/76. Nevertheless, the program’s banking transactions are impeded by financial audits beginning in 2073 due to the COVID-19 pandemic. Despite playing a significant role in local development, an emphasis on financial management and regulation is necessary for increased policy effectiveness in ensuring long-term poverty reduction strategies.